Optimizing treatment for lymphoma in cats - SuprunenkoО. О.; Kovalenko, M. S.; Bilyi, D. D.; Hrebeniuk, K. R.; Stotskyi, O. G. (Regulatory Mechanisms in Biosystems, 2026)
The role of antibacterial agents within lymphoma treatment protocols remains unresolved in both human and vete r inary medicine. The present study aimed to evaluate the clinical efficacy of combining the COP protocol (vincristine, cyclophosphamide, and prednisolone) with azithromycin in cats with lymphoma. The results demonstrated that the addition of azithromycin to the chemotherapy protocol increased median overall survival by 20% and median progre s sion-free survival by 30%. Furthermore, incorporation of azithromycin into the treatment regimen led to a 30% increase in complete response rates, accompanied by a twofold reduction in the risk of disease progression. Importantly, azithr o mycin administration did not increase the incidence of adverse effects; on the contrary, it reduced the proportion of patients exhibiting vomiting, diarrhoea, and lymphopenia by 2.4-fold (from 29.2% to 12.5%). In cats with lymphoma and concurrent FeLV-positive status, the combination of the COP protocol (vincristine, cyclophosphamide, and predn i solone) with azithromycin resulted in a 30% increase in median survival (from 156 to 201 days) and prolonged time to disease progression by 30% (from 102 to 136 days). The combined use of vincristine, cyclophosphamide, prednisolone, and azithromycin was associated with improved clinical outcomes across all disease stages, as evidenced by a 20% increase in median survival. Given the multisystemic nature of feline lymphoma and the systemic effects of azithrom y cin, its use may represent a promising adjunctive therapeutic strategy. Further studies are warranted to investigate its clinical efficacy in greater detail, including its safety profile and the underlying pathogenetic mechanisms of its action on both primary tumours and metastatic lesions.